Answer:
1. x=0
2. m=5
3. x=8
4. x=-8
5. x=49
6. x=-133
Step-by-step explanation:
1. 9x=0
2. -20=-4m, 20=4m
3. 2x=16
4. x/8=-1, x=-1x8
5. x/7=7
6. After simplifying: −1/19(x)=7
Hope this helped, I just simplified all the steps for the step by step explanation. Have a great day and stay safe, happy, and healthy!
Step-by-step explanation:
Y is equal to:
2/3x - 2 = 10
2/3x = 10 + 2
2/3x = 12
3/3x = (12 ÷ 2) × 3
x = 18
Not sure but its worth a try.
The inverse of function f(x) = 9x+7 is f-1(x) = x/9 - 7/9
<h3>How to determine the inverse of the function?</h3>
The function is given as:
f(x) = 9x + 7
Express f(x) as y
y = 9x + 7
Swap the positions of x and y in the above equation
x = 9y + 7
Subtract 7 from both sides
9y = x - 7
Divide through by 9
y = x/9 - 7/9
Express as an inverse function
f-1(x) = x/9 - 7/9
Hence, the inverse of function f(x) = 9x+7 is f-1(x) = x/9 - 7/9
Read more about inverse functions at:
brainly.com/question/14391067
#SPJ1
Answer:
A, C and E are true.
Step-by-step explanation:
The domain is a set of natural numbers.
The recursive formula is correct:
When x = 1, f(x) = 4 and f(x + 1) = f(2) = 3/2 f(x) = 3/2 * 4 = 6.
It is also true for the other points on the graph.
D is incorrect.
E is correct exponential growth with the formula 4(3/2)^(x-1).
The equation would be y = 3x-3